The experience of immersive virtual reality in patients with heart failure during cardiac rehabilitation: a qualitative study - Micheluzzi, Valentina; Casu, Gavino; Burrai, Francesco; Canu, Antonella; Sircana, Antonio; Merella, Pierluigi; Laconi, Angelo; Chelo, Andrea; Cozzula, Piero; Piredda, Michela; Vellone, Ercole (Frontiers in Medicine, 2025)
BackgroundTo alleviate symptoms and reduce adverse outcomes associated with heart failure, international guidelines strongly recommend cardiac rehabilitation. However, patient adherence to rehabilitation programs remains suboptimal, leading to unfavorable effects on key cardiac outcomes. Immersive virtual reality (iVR) is a promising intervention to improve adherence to cardiac rehabilitation and enhance clinical outcomes. This study aims to explore patients’ experiences with iVR during cardiac rehabilitation.MethodsA qualitative descriptive study was embedded within a randomized controlled two-arm trial involving twenty-two patients who were referred to undergo eight cardiac rehabilitation sessions, held twice a week for 30 min each. The intervention group experienced iVR in natural settings, while the control group received standard care. Semi-structured individual interviews were conducted in person after the intervention group’s eighth rehabilitation session. These interviews were audio-recorded, transcribed verbatim, and analyzed using content analysis.ResultsData from twenty-two interviews reached saturation. Content analysis generated four main categories and nine subcategories: (1) cognitive and emotional benefits of iVR (acceptability and enrichment of the rehabilitation experience, positive emotions, cognitive engagement); (2) impact on rehabilitation (physical engagement, perceived effort); (3) customizable intervention (variety of scenarios, quality and beauty of the videos); (4) negative aspects of the iVR (discomfort with the equipment, negative feelings toward the iVR devices).ConclusionIVR is an innovative and customizable intervention that enhances the rehabilitation experience by providing cognitive, emotional, and physical benefits. It improves key aspects of rehabilitation, including time perception, motivation, enjoyment, effort perception, and anxiety management, highlighting its potential in cardiac rehabilitation. However, certain technological challenges, such as discomfort with the equipment, must be addressed to optimize the user experience.